La bienveillance en éducation : un défi pédagogique - Renaud Hétier (Éducation et Socialisation)
Today, there is a lot of interest in benevolence, in the political and ethical fields (with the ethics of care in particular) and in the educational field, with official texts that make it an aim of the school, various research studies and publications for the general public having a lot of echo. This emergence is not accidental: it is at the crossroads of various developments: children's rights, liberation of victims' speech, certain specificities of school suffering taken into account, in particular. Of course, corporal retribution is forbidden and humiliating or mind-numbing punishments are no longer acceptable. However, an invisible violence (in a grey zone) can remain at school, which can be either a stigmatization of the child (because of his behavior or difficulties), especially from a verbal perspective, or an ostracization. The concern for benevolence should therefore be taken seriously, as an attempt to remedy this background of violence. But it must also be examined with caution, insofar as it may obscure the essential stake of the school, which is that of a linking with knowledge, and the development of abilities. "Good relationships" cannot save a missed opportunity to meet this challenge. Hence the importance of re-examining the requirements of a overall pedagogy, a political pedagogy, which fully articulates the respect of the child and the stimulation of his power of action.